Analysis of Turkey’s Innovation Performance in Pandemic Times: Comparison of The Performances in Pre-pandemic and Pandemic Tımes (2019–2021) - Köksal, Mustafa Serdar (National Research and Innovation Agency, Indonesia, 2023)
Innovation performance of developing countries is a fundamental factor for reaching sustainable economies. Turkey as a developing country should be monitored in terms of its innovation performance due to its vulnerable economy to global changes such as pandemic. In this study, investigation of different data sets from Europe and Turkey was done in terms of changes in human resources, firm investments, digitalization, number of R&D personals, R&D expenditure and number of approved patents by considering pandemic years. The results showed that significant decrease in number of innovators and innovation index after 2020. Moreover, firm investments regarding innovation decreased after 2020 while digitalization represented continuous increase during 8 years involving pandemic years. In addition, number of patens approved by authorities and number of R&D personnel have been increasing over time in spite of the pandemic, but R&D expenditure and innovation performance have not been changing in similar trend. The findings revealed that Turkey has been making improvements on number of R&D personnel, digitalization and number of patents in spite of the pandemic, however expected increases in innovation index value, R&D expenditure and number of innovators were not observed during the pandemic years. The findings of this study might contribute to policy makers for recovery of economy of Turkey after the pandemic.